Planning of Low Voltage Electricity Distribution at Griya Arjuna Kejuden Housing - Deni Wachyudin; Amy Fahmy Ardiansyah; Mohammad Soleh; Agus Siswanto (Mestro, 2022)
In a low-voltage power distribution system, there are often disturbances that result in disruption of electricity distribution to customers, resulting in losses for customers and PLN. The problem that often occurs is the occurrence of voltage drops and power losses so that in planning the construction of a low-voltage electric power distribution network, it is necessary to anticipate the occurrence of these problems. This research is expected to be used as a lesson for the creation of a low-voltage electric power distribution network with suitable and environmentally friendly construction and with low investment costs. collected data by visiting the location to conduct a survey and obtain accurate data related to the state of the research location. The stages in planning the Low Voltage Electricity Distribution Network begin with a field survey to obtain the required data. The installed power for each unit is 1.300 VA, so the total installed power is 122,200 VA and the spare power is 5% of the installed power so that the total installed power is 128.310 VA. during peak load times it is estimated that power consumption will only absorb 80% or 97,760VA. The required substation is a Portal Type Pole with a transformator capacity is 160kVA. The total breakdown of the electricity distribution network budget at the Griya Arjuna Kejuden is IDR 382,333,141.